2016
DOI: 10.1590/1516-3180.2015.02581002
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for choosing the specialty of Family Medicine from undergraduate knowledge and attitudes

Abstract: CONTEXT AND OBJECTIVE: A cold climate towards primary care (PC) within medical academia could form a barrier against choosing family medicine (FM) as a career option. This study was designed to determine whether medical students' knowledge of and attitudes towards FM predicted their career choice. RESULTS: In Albacete, the questionnaire was answered by 79 second-year and 76 sixth-year students; in Seville, it was answered by 26 sixth-year students. After completing the PC course, 69.3% said they would like to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
1
6
0
2
Order By: Relevance
“…Results of this study seemed to be consistent with previous findings [13]. This work contributes to the many studies that have been published on the interest of medical students in FM with the strength of a prospective study, following-up from two cohorts of students in the second year and sixth years as well as after speciality election.…”
Section: Discussionsupporting
confidence: 90%
“…Results of this study seemed to be consistent with previous findings [13]. This work contributes to the many studies that have been published on the interest of medical students in FM with the strength of a prospective study, following-up from two cohorts of students in the second year and sixth years as well as after speciality election.…”
Section: Discussionsupporting
confidence: 90%
“…The stability of the participants’ preferences obtained in cross-sectional research remains uncertain. The optimism for interest in GP should be interpreted with caution, as the international literature suggests that without an unequivocal social valuing of GP, interest will likely wane as these students progress through the curriculum 8,13,14,31. As the study was conducted in a leading academic medical institution, caution may be needed in extrapolating the findings across China.…”
Section: Discussionmentioning
confidence: 99%
“…Conviction based on personal experience with illness in oneself or others has been shown to influence GP career choice,7,11 though expectations for higher income, prestige, and a research career have been negatively associated with primary care interest 4. Student attitudes toward GP have been illustrated to be more positive in countries with social policies favoring primary care, eg, the UK and Spain,6,12 than countries without primary care-supportive policies, eg, Brazil and Germany 13,14…”
Section: Introductionmentioning
confidence: 99%
“…Of course, studies in Canada and Australia, however, have shown that in recent years, the number of medical school graduates choosing a family physician as a specialty has declined because of the load of working and payment problems. [ 60 61 ]…”
Section: Discussionmentioning
confidence: 99%